Qualitative data analysis practical strategies - Bazeley, Pat (SAGE, 2013)
A one-stop-shop for anyone who has collected, or is about to collect, data. The definitive step-by-step guide to qualitative data analysis, this is full of practical strategies from a world renowned researcher